Radical digital agency as a foundation for just and sustainable smart cities - Ylipulli, Johanna; Hämäläinen, João; Palo, Ella (Human Technology, 2025)
The article examines the relationship between smart city development, socio-digital inequality, and digital literacy. Furthermore, we investigate the link between city residents’ digital competence and so-called smart citizenship. Through these theoretical explorations, we aim to demonstrate the importance of a more in-depth understanding of digital inequality in the context of people-centric smart cities. We then use examples from our hybrid ethnographic fieldwork in Barcelona to show how these perspectives might manifest in practical applications. Barcelona aspires to be the capital of ’technological humanism’ and, in recent years, has implemented a number of digital inclusion initiatives. Based on the theoretical discussion and empirical results, we present a framework that combines the theoretical framing and empirical findings, highlighting the intersecting factors that policymakers and educators must consider when developing just and sustainable smart cities.